Prenatal and early postnatal lead exposure and later adulthood BMI: The Saint Louis baby tooth – Later life health study - Joyce J.Y. Lin; Ruby Hickman; Michael Leung; Justin Farmer; Ian W. Tang; Kaleigh McAlaine; Tracy Punshon; Brian P. Jackson; Felicitas B. Bidlack; Joseph J. Mangano; Marc G. Weisskopf (Environmental Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Pre- and postnatal exposure to PM2.5 and NO2 and blood pressure in children: Results from the ECHO Cohort - Yu Ni; Andrew Law; Xingyu Gao; Adam A. Szpiro; Christine T. Loftus; Miranda Jones; Logan C. Dearborn; Marnie F. Hazlehurst; Allison R. Sherris; Sindana Ilango; Kaja Z. LeWinn; Nicole R. Bush; et al. (Environmental Research, 2026)

Gestational fine particulate matter exposure and perinatal outcomes in the ECHO cohort: Associations across pregnancy windows - Adaeze W. Nzegwu; Aisha S. Dickerson; Kristin Miller; Adam Szpiro; Alison E. Hipwell; Amy J. Elliot; Amy M. Padula; Anne L. Dunlop; Anne P. Starling; Assiamira Ferrara; Carrie V. Breton; Christine T. Loftus; et al. (Environmental Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Acute UV response of early erythema and late edema in SKH1 mice - Szabolcs Bozsányi; Rhea Carmel Glen Rodrigues; Ruby Acquah; Erin C. Tracy; Sean P. Murphy; Jocelyn Tracy; Li Yan; Mehdi Boostani; Hamid-Reza Rezvani; Wendy J. Huss; Gyorgy Paragh (Journal of Photochemistry and Photobiology B: Biology, 2026)

Integrated Body and Otolith Morphometrics Indicate a Single Stock of Bigeye Scad (Selar crumenophthalmus) in Northern Mindanao, Philippines - Renie M. Magallanes; Lhendy P. De Leon; Rosa Ruby P. Cabiguin; Emmanuel S. Delloro; Adzel Adrian G. Baldevieso; Kaent Immanuel N. Uba (Thalassas: An International Journal of Marine Sciences, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Influence of raceway based biofloc system on the growth and physiological responses of Penaeus vannamei and GIF tilapia in a polyculture model – BFT aquaculture system - M Joshna; Ahilan B; Cheryl Antony; Ravaneswaran K; Chidambaram P; Uma A; Ruby P; Prabu E; Somu Sunder Lingam R (Aquacultural Engineering, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

When outsiders are resource users: Fishers’ migration in Southwest Panay, Philippines, and its impact on small-scale fisheries - Liberty N. Espectato; Ruby P. Napata; Juhn Chris Espia; Alice Prieto-Carolino (Ocean & Coastal Management, 2024)

Species tree analyses and speciation-based species delimitation support new species in the relict catfish family Diplomystidae and provide insights on recent glacial history in Patagonia - Carlos P. Muñoz-Ramírez; Nicole Colin; Cristian B. Canales-Aguirre; Aliro Manosalva; Ruby López-Rodríguez; Jeet Sukumaran; Konrad Górski (Molecular Phylogenetics and Evolution, 2023)

Hydrolysate production from sugarcane bagasse using steam explosion and sequential steam explosion-dilute acid pretreatment for polyhydroxyalkanoate fermentation - Hazel Joy C. Barrameda; Princess J. Requiso; Catalino G. Alfafara; Fidel Rey P. Nayve Jr.; Ruby Lynn G. Ventura; Jey-R S. Ventura (Bioactive Carbohydrates and Dietary Fibre, 2023)

Modern biotic and abiotic analogues from the surface soil of Ganga-Ghaghara-Gandak interfluves of the Central Ganga Plain (CGP), India: Implications for the palaeoecological reconstructions - Swati Tripathi; Biswajeet Thakur; Anupam Sharma; Binita Phartiyal; Sadhan Kumar Basumatary; Ruby Ghosh; Kamlesh Kumar; M.C. Manoj; Shailesh Agrawal; Anjum Farooqui; Pooja Tiwari; Korobi Saikia; et al. (CATENA, 2023)

The population structure, sex ratio and reproductive potential of limpets (Patella spp.) on natural shores and artificial structures in the Irish Sea - Hannah S. Earp; Ruby George; Paul R. Brooks; Veronica Farrugia Drakard; Bryan J. Thompson; Benjamin Fisher; Róisín Hayden; Tasman P. Crowe; Pippa J. Moore (Marine Environmental Research, 2023)

Last 10 millennial history of Indian summer monsoon in the Bengal region – a multi-proxy reconstruction from a lacustrine archive - Ruby Ghosh; Korobi Saikia; Oindrila Biswas; Shailesh Agrawal; P. Morthekai; Mohammad Arif; Binita Phartiyal; Anupam Sharma; Neha Singh; Dipak Kumar Paruya; Pyarimohan Maharana; Mayank Shekhar; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Seaweed ethnobotany of eastern Sorsogon, Philippines - Richard V. Dumilag; Teresa Haide R. Belgica; Lynn C. Mendoza; Janet M. Hibay; Abel E. Arevalo; Mark Ariel D. Malto; Elden G. Orgela; Mabille R. Longavela; Laurence Elmer H. Corral; Ruby D. Olipany; Caesar Franz C. Ruiz; Cynthia B. Mintu; et al. (Algae, 2022)
Knowledge on the seaweeds of eastern Sorsogon in the Philippines is uneven. Not only is eastern Sorsogon among the areas of high seaweed diversity but locals there have interacted with seaweeds for ages. Despite seaweeds’ assumed importance to Sorsoganon, ethnobotanical records are missing. In this study, we documented the traditional knowledge on seaweed use and determined the rate of knowledge transmission among the locals of eastern Sorsogon. Vernacular names and modes of preparation were given of the 12 identified species bearing culinary and medicinal importance. Ten species were eaten while three were used therapeutically. Based on ethnobotanical indices, Caulerpa chemnitzia ecad turbinata and Gelidiella acerosa were the most important seaweeds. The least cited was Caulerpa racemosa. Our study demonstrated that most of the seaweed resources in eastern Sorsogon remain largely untapped, as the identified ethnotaxa were only about 5% of the total seaweed species diversity reported for the area. The seaweed knowledge in eastern Sorsogon appeared to be homogenous across age groups with primary sources of knowledge biased towards female relatives (mothers and grandmothers) and to children as inheritors. Cessation of seaweed knowledge may come at a potential cost, as a significant fraction of the population did not transmit their knowledge to others. Our study furthered the interest in providing sophisticated resource management recommendations that consider the relationships of traditional and scientific knowledge of seaweed selection and use in eastern Sorsogon and beyond.

First report of fruit rot of jackfruit caused by Athelia rolfsii in India - Abdulmajeed Sajeena; Deepu Mathew; Jacob John; M. K. Dhanya; K. Sushitha; P. Ruby Nahan (Journal of Plant Pathology, 2022)

A comprehensive review of dye-sensitized solar cell optimal fabrication conditions, natural dye selection, and application-based future perspectives - Ruby Baby; Peter Daniel Nixon; Nallapaneni Manoj Kumar; M. S. P. Subathra; Nallamuthu Ananthi (Environmental Science and Pollution Research, 2022)

Outdoor/Indoor Contaminant Transport by Atmospheric Dust and Aerosol at an Active Smelter Site - Tania B. Rodríguez-Chávez; Kyle P. Rine; Reman M. Almusawi; Ruby O’Brien-Metzger; Mónica Ramírez-Andreotta; Eric A. Betterton; A. Eduardo Sáez (Water, Air, & Soil Pollution, 2021)

Progress on the phylogeny of the Omphalotaceae: Gymnopus s. str., Marasmiellus s. str., Paragymnopus gen. nov. and Pusillomyces gen. nov. - Jadson J. S. Oliveira; Ruby Vargas-Isla; Tiara S. Cabral; Doriane P. Rodrigues; Noemia K. Ishikawa (Mycological Progress, 2019)

Workers' sons rescue genetic diversity at the sex locus in an invasive honey bee population - Rosalyn S. Gloag; Joshua R. Christie; Guiling Ding; Ruby E. Stephens; Gabriele Buchmann; Benjamin P. Oldroyd (Molecular Ecology, 2019)
The hallmark of eusociality is the division of labour between reproductive (queen) and nonreproductive (worker) females. Yet in many eusocial insects, workers retain the ability to produce haploid male offspring from unfertilized eggs. The reproductive potential of workers has well‐documented consequences for the structure and function of insect colonies, but its implications at the population level are less often considered. We show that worker reproduction in honey bees can have an important role in maintaining genetic diversity at the sex locus in invasive populations. The honey bee sex locus is homozygous‐lethal, and, all else being equal, a higher allele number in the population lead to higher mean brood survival. In an invasive population of the honey bee Apis cerana in Australia, workers contribute significantly to male production: 38% of male‐producing colonies are queenless, and these contribute one‐third of all males at mating congregations. Using a model, we show that such male production by queenless workers will increase the number of sex alleles retained in nascent invasive populations following founder events, relative to a scenario in which only queens reproduce. We conclude that by rescuing sex locus diversity that would otherwise be lost, workers' sons help honey bee populations to minimize the negative effects of inbreeding after founder events and so contribute to their success as invaders.

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

Biopharmaceutical considerations and characterizations in development of colon targeted dosage forms for inflammatory bowel disease - Rajkumar Malayandi; Phani Krishna Kondamudi; P. K. Ruby; Deepika Aggarwal (Drug Delivery and Translational Research, 2014)

Effects of agricultural pesticides on the health of Rana pipiens frogs sampled from the field - M. S. Christin; L. Ménard; I. Giroux; D. J. Marcogliese; S. Ruby; D. Cyr; M. Fournier; P. Brousseau (Environmental Science and Pollution Research, 2013)

Treatment of hydrocarbon contamination under flow through conditions by using magnetite catalyzed chemical oxidation - M. Usman; P. Faure; C. Lorgeoux; C. Ruby; K. Hanna (Environmental Science and Pollution Research, 2013)

Polyphyly of non‐bioluminescent Vibrio fischeri sharing a lux ‐locus deletion - M. S. Wollenberg; S. P. Preheim; M. F. Polz; E. G. Ruby (Environmental Microbiology, 2012)
Summary This study reports the first description and molecular characterization of naturally occurring, non‐bioluminescent strains of Vibrio fischeri . These ‘dark’ V. fischeri strains remained non‐bioluminescent even after treatment with both autoinducer and aldehyde, substrate additions that typically maximize light production in dim strains of luminous bacteria. Surprisingly, the entire lux locus (eight genes) was absent in over 97% of these dark V. fischeri strains. Although these strains were all collected from a Massachusetts (USA) estuary in 2007, phylogenetic reconstructions allowed us to reject the hypothesis that these newly described non‐bioluminescent strains exhibit monophyly within the V. fischeri clade. These dark strains exhibited a competitive disadvantage against native bioluminescent strains when colonizing the light organ of the model V. fischeri host, the Hawaiian bobtail squid Euprymna scolopes . Significantly, we believe that the data collected in this study may suggest the first observation of a functional, parallel locus‐deletion event among independent lineages of a non‐pathogenic bacterial species.

ENSO anomalies over the Western United States: present and future patterns in regional climate simulations - Yongxin Zhang; Yun Qian; Valérie Dulière; Eric P. Salathé; L. Ruby Leung (Climatic Change, 2012)

Simulations of precipitation using NRCM and comparisons with satellite observations and CAM: annual cycle - Aditya Murthi; Kenneth P. Bowman; L. Ruby Leung (Climate Dynamics, 2011)

Regional climate model projections for the State of Washington - Eric P. Salathé; L. Ruby Leung; Yun Qian; Yongxin Zhang (Climatic Change, 2010)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Exposure of leopard frogs to a pesticide mixture affects life history characteristics of the lungworm Rhabdias ranae - A. D. Gendron; D. J. Marcogliese; S. Barbeau; M.-S. Christin; P. Brousseau; S. Ruby; D. Cyr; M. Fournier (Oecologia, 2003)

Characterization of Microbial Communities from Coastal Waters using Microarrays - O. Colin Stine; Amy Carnahan; Ruby Singh; Jan Powell; Jon P. Furuno; Alicia Dorsey; Ellen Silbergeld; Henry N. Williams; J. Glenn Morris (Environmental Monitoring and Assessment, 2003)

Chemical Composition of Fruits and Leaves Eaten by Short-Nosed Fruit Bat, Cynopterus sphinx - J. Ruby; P. T. Nathan; J. Balasingh; T. H. Kunz (Journal of Chemical Ecology, 2000)

Sublethal Lead Affects Pituitary Function of Rainbow Trout During Exogenous Vitellogenesis - S. M. Ruby; R. Hull; P. Anderson (Archives of Environmental Contamination and Toxicology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Cryptic luminescence in the cold-water fish pathogen Vibrio salmonicida - P. M. Fidopiastis; Henning Sørum; E. G. Ruby (Archives of Microbiology, 1999)

Tuber yield, soft rot resistance, bruising resistance and processing quality in a population of potato (cv. crystal) somaclones - R. J. Taylor; G. A. Secor; C. L. Ruby; P. H. Orr (American Journal of Potato Research, 1993)